Purchase and consumption habits for quinoa and amaranth in Brazil - SCHMIDT, Davi; BORGES, Maria Teresa Mendes Ribeiro; FORTI, Victor Augusto; GALLO, Anderson de Souza; VERRUMA-BERNARDI, Marta Regina (Food Science and Technology, 2024)
A large amount of information about consumer profile can be obtained when consumption habits are observed. Thus, the aim of this work was to identify the profile of consumers and their consumption habits in relation to quinoa and amaranth in Brazil. Data were collected through an online questionnaire survey method, covering aspects such as consumer profile, knowledge and consumption of quinoa and amaranth, diet diversification, and packaging preferences. Within two months, 520 responses were obtained. Around 90% of participants knew quinoa and 43% knew amaranth. High nutritional quality and diet diversification were the main motivations for the consumption of these pseudocereals, and the purchase of these products in grains and in bulk were the most common forms of commercialization among participants. Despite quinoa being more widely consumed, it was concluded that most participants were interested in including amaranth in their diets. A broader dissemination of these foods could contribute to their inclusion in the diet of an increasing number of people.